CONDITIONS FOR THE FORMATION OF FLOODS IN THE TERRITORY OF CENTRAL KAZAKHSTAN - Рагимовна, Салтанат; Алагуджаева , Манира; Ельбасиева, Балжан (Hydrometeorology and ecology, 2023)
This article presents the results of the analysis of the causes of the formation of floods in the basins of the Nura and Yesil rivers in the territory of the Republic of Kazakhstan for the period 1960-2023 in the conditions of modern climatic changes. It is shown that the duration of the flood and the rivers of the Nur-Sarys basin depends on the size of the basin, its forest cover, swampiness, the presence of lakes, the amount of snow reserves at the beginning of the flood and the nature of spring.